The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/agronomy11122388
|View full text |Cite
|
Sign up to set email alerts
|

Plant Disease Identification Using Shallow Convolutional Neural Network

Abstract: Various plant diseases are major threats to agriculture. For timely control of different plant diseases in effective manner, automated identification of diseases are highly beneficial. So far, different techniques have been used to identify the diseases in plants. Deep learning is among the most widely used techniques in recent times due to its impressive results. In this work, we have proposed two methods namely shallow VGG with RF and shallow VGG with Xgboost to identify the diseases. The proposed model is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…With the development of computer vision technology, pattern recognition has been widely used in plant disease diagnosis [5]. The traditional plant disease diagnosis methods include features extraction and analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer vision technology, pattern recognition has been widely used in plant disease diagnosis [5]. The traditional plant disease diagnosis methods include features extraction and analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are more than a dozen different diseases of tomato plants in practice, so it is essential to detect them as accurately and as early as possible to prevent and treat the disease [3,4]. There are different methods of detecting plant diseases for different treatment, including those that use artificial intelligence (AI) algorithms of SVM based on image futures or neural networks (NNs) [5][6][7]. It is obvious that AI techniques have been applied in many fields of agriculture to identify plant diseases such as apple, tomato, and rice; others have used deep learning networks, which will be applied in this research for classifying tomato leaf diseases [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, such adaptive systems have a serious drawback, they cannot be customized to the individual characteristics of each root crop. In digital agriculture [10,11], computer vision systems are used to quickly detect and count plants [12][13][14][15], to determine their ripeness and diseases [16][17][18][19][20], as part of systems to protect against weeds and pests [21,22], to determine the position of cattle [23]. In recent years publications have shown that the problem of identifying diseased or mechanically damaged fetuses on transportation systems such as conveyor belts, drums, turbines and etc.…”
Section: Introductionmentioning
confidence: 99%